2021
DOI: 10.1016/j.scitotenv.2020.142872
|View full text |Cite
|
Sign up to set email alerts
|

Oil spill + COVID-19: A disastrous year for Brazilian seagrass conservation

Abstract: The COVID-19 pandemic has been the greatest global public health threat of the 21 st century. Additionally, it has been challenging for the Brazilian shores that were recently (2019/2020) affected by the most extensive oil spill in the tropical oceans. Monitoring programs and studies about the economic, social and ecological consequences of the oil disaster were being carried out when the COVID-19 (coronavirus disease 2019) pandemic was declared, which has heavily affected Brazil. For Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 41 publications
0
38
0
3
Order By: Relevance
“…Notwithstanding the adaptive capacity of many species, it is observed that climate change impacts on the ocean biota, and warming, sea level rise, and acidification lead to the loss of biogenic reefs, mangroves, algae and seagrass beds (OPPENHEIMER et al, 2014;CRAMER et al, 2015;MAGALHÃES et al, 2020). Likewise, failing to intervene on human behavior feed a vicious cycle that compromises the ocean's ability to contribute to climate regulation (HORTA et al, 2018), as well as interactions and interdependencies of continental ecosystems (LEYBA et al, 2019;MARENGO et al, 2019).…”
Section: Potential Distribution Modellingmentioning
confidence: 99%
“…Notwithstanding the adaptive capacity of many species, it is observed that climate change impacts on the ocean biota, and warming, sea level rise, and acidification lead to the loss of biogenic reefs, mangroves, algae and seagrass beds (OPPENHEIMER et al, 2014;CRAMER et al, 2015;MAGALHÃES et al, 2020). Likewise, failing to intervene on human behavior feed a vicious cycle that compromises the ocean's ability to contribute to climate regulation (HORTA et al, 2018), as well as interactions and interdependencies of continental ecosystems (LEYBA et al, 2019;MARENGO et al, 2019).…”
Section: Potential Distribution Modellingmentioning
confidence: 99%
“…Some Brazilian States, after experienced some difficulties, have exhibited integrated coordination with non-governmental organizations, the military, civil society, universities, and Brazilian municipalities and searched, as much as possible, to provide science-based actions during the disaster. The geographic extension of the incident and the social, economic, and ecological impacts standout the 2019/2020 event as the worst environmental disaster in Brazilian history and the most extensive ever recorded in the tropical oceans (Magalhães et al 2021;Soares et al 2020a, b).…”
Section: Introduction: the Underrated And Mysterious Oil Spill In The South Atlantic Oceanmentioning
confidence: 99%
“…A growing body of evidence in the scientific literature suggests the pandemic is having mixed effects on wildlife populations (Manenti et al, 2020 ; Rondeau, Perry, & Grimard, 2020 ). Negative impacts stemming from COVID‐19 shutdowns include increases in some air pollutants (Higham, Ramirez, Green, & Morse, 2020 ), increases in traffic noise levels due to fewer but faster moving vehicles (Stokstad, 2020 ), increased illegal activity due to a reduction in law enforcement (Manenti et al, 2020 ), and reduction or halting of conservation programs (Magalhães et al, 2020 ). However, evidence of immediate net positive effects on wildlife are numerous and include detection of rare species in urban areas suggesting possible range expansion (Silva‐Rodríguez, Gálvez, Swan, Cusack, & Moreira‐Arce, 2021 ; Simon, 2020 ; Stokstad, 2020 ), exploitation of newly available resources (Derryberry, Phillips, Derryberry, Blum, & Luther, 2020 ), and improved recruitment and survivorship (Manenti et al, 2020 ; Shilling et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%